Health Education on the Importance of Exclusive Breastfeeding as the Main Nutrition for Infants 0-6 Months in Kolono Village: Penyuluhan Kesehatan tentang Pentingnya ASI Eksklusif sebagai Nutrisi Utama Bayi 0 – 6 Bulan di Desa Kolono - Dian Rosmala Lestari; Sitti Alengo (Jurnal Pengabdian Bidan Nasuha, 2023)
Mother's milk is the main nutrition for babies, especially at the age of 0-6 months which is safe, clean, and contains antibodies to protect against disease. WHO and UNICEF recommend breastfeeding only for children aged 6 months. Purpose: to increase mother's knowledge about exclusive breastfeeding. Method: this community service is carried out by providing counseling and distributing pretest and posttest questionnaires with a total of 30 participants. Result: after counseling there is an increase in knowledge about the importance of exclusive breastfeeding. Suggestion: to do counseling related to exclusive breastfeeding at antenatal care visits, especially for primigravida mothers. So it is hoped that this service will increase the mother's knowledge and can increase the motivation of mothers to provide exclusive breastfeeding.